Penggunaan Teknik Peminjaman dalam Penerjemahan Teks Informatif tentang Digitalisasi di Majalah Dwibahasa Jerman-Indonesia “NADI” - Alif Nadia Indah; Rosyidah (Nexus Publishing, 2024)
This study aimed to analyze the use of naturalized borrowing technique in the translation of informative texts about digitalization in NADI magazine. The method used in this research is descriptive qualitative. The German-Indonesian bilingual magazine NADI was the data source of this research. The data collected were words with the theme of digitalization in German that were translated into Indonesian using the naturalized borrowing technique. The researcher was the main instrument in this research and the documentation table was used as a data collection instrument with the reading and note-taking technique. The data analysis technique applied in this research was the Miles & Huberman (1992) model technique. The results show that there are 28 words translated with naturalized borrowing technique and classified into 11 sub-classifications, namely letter change (same sound), letter and sound change, suffix change -(t)ion to -si, change of suffix -ierung to -ization, change of suffix -ell to -al, change of suffix -isch to -is, change of writing -tät to -tas, change of suffix -mus to -me, double consonant, change of letter z to letter s, and omission of letter t at the end of the word. There are two main reasons for the use of naturalized borrowing techniques, namely the theme of the text which is closely related to technology, namely digitalization (Digitalisierung) and the familiarity and preference of language users.